2012
DOI: 10.1038/ng.2202
|View full text |Cite
|
Sign up to set email alerts
|

Complex reorganization and predominant non-homologous repair following chromosomal breakage in karyotypically balanced germline rearrangements and transgenic integration

Abstract: We defined the genetic landscape of balanced chromosomal rearrangements at nucleotide resolution by sequencing 141 breakpoints from cytogenetically-interpreted translocations and inversions. We confirm that the recently described phenomenon of “chromothripsis” (massive chromosomal shattering and reorganization) is not unique to cancer cells but also occurs in the germline where it can resolve to a karyotypically balanced state with frequent inversions. We detected a high incidence of complex rearrangements (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
271
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(298 citation statements)
references
References 41 publications
13
271
0
10
Order By: Relevance
“…Le chromothripsis pourrait ne pas être un événement unique et isolé, mais faire partie d'un mécanisme plus complexe et dynamique de gestion de l'instabilité génomique. Des expériences de simulation du chromothripsis dans des cellules en culture sont en cours [16], et des modèles in silico sont à l'étude pour mieux caractériser les chromothripsis et mieux comprendre les mécanismes qui pilotent leur apparition [49]. D'un point de vue clinique, l'application des nouvelles techniques de séquençage à haut débit de l'ADN pour l'analyse des remaniements chromosomiques constitutionnels va sans doute révéler l'importance du chromothripsis dans l'émergence de nombreux désordres congénitaux, alors qu'en cancérologie, le lien découvert entre le chromothripsis et le dysfonctionnement du gène TP53 pourrait ouvrir de nouvelles voies thérapeu-tiques.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Le chromothripsis pourrait ne pas être un événement unique et isolé, mais faire partie d'un mécanisme plus complexe et dynamique de gestion de l'instabilité génomique. Des expériences de simulation du chromothripsis dans des cellules en culture sont en cours [16], et des modèles in silico sont à l'étude pour mieux caractériser les chromothripsis et mieux comprendre les mécanismes qui pilotent leur apparition [49]. D'un point de vue clinique, l'application des nouvelles techniques de séquençage à haut débit de l'ADN pour l'analyse des remaniements chromosomiques constitutionnels va sans doute révéler l'importance du chromothripsis dans l'émergence de nombreux désordres congénitaux, alors qu'en cancérologie, le lien découvert entre le chromothripsis et le dysfonctionnement du gène TP53 pourrait ouvrir de nouvelles voies thérapeu-tiques.…”
Section: Resultsunclassified
“…Toutes ces observations ont remis en question les modèles classiques de cancéroge-nèse, basés sur l'acquisition progressive, ou par paliers, de multiples remaniements chromosomiques indépendants les uns des autres, et s'accumulant au fil du temps pour constituer une population de cellules malignes [11]. de maladies congénitales et porteurs de réarrangements chromosomiques complexes [15], mais aussi chez des sujets porteurs de translocations ou d'inversions simples [16], avec, dans tous les cas, une nette prédominance de l'origine paternelle de ces remaniements.…”
Section: La Découverte Du Chromothripsisunclassified
“…Data processing and analysis were performed as previously described (Figure 2a). 10,11 Targeted locus amplification library A targeted locus amplification library was prepared as previously described. 12 In brief, genomic DNA was crosslinked, enzymatically digested and then re-ligated to create circularized DNA fragments.…”
Section: Whole-genome Jumping Librarymentioning
confidence: 99%
“…4 Surprisingly, many disease-associated chromosomal rearrangements initially characterized as simple turned out to be more complex than first predicted, revealing a new catastrophic phenomenon of local chromosome shattering termed "chromothripsis" (CTH). [5][6][7][8][9][10] CTH was first characterized in cancerous tissue in which up to hundreds of DNA breaks were localized in relatively small genomic regions and the copy-number states oscillated between one and two (and occasionally three). 5,7 It has been suggested that, in contrast to the progressive model of accumulating mutations in cancer, where rearrangements occur sequentially and independently over many cell cycles, the catastrophic event of CTH happens in a single cell cycle, with profound implications for the etiology of some cancer types.…”
Section: Introductionmentioning
confidence: 99%